A review of the John F. Kennedy Medical Center's response to the COVID-19 pandemic in Liberia - Wachekwa, Ian; Camanor, Sia Wata; Kpoeh-Thomas, Tete; Glaydor, Facia; Barclay-Korboi, Yassah Moracious; Moses, J. Soka; Bartekwa-Gwaikolo, Joyce Weade (Frontiers in Public Health, 2024)
Objective: Over the past decades, the world has experienced a series of emerging and reemerging infectious disease pandemics with dire consequences on economies and healthcare delivery. Hospitals are expected to have the ability to detect and respond appropriately to epidemics with minimal disruptions to routine services. We sought to review the John F. Kennedy Medical Center's readiness to respond to the COVID-19 pandemic.We used a pretest-posttest design in June 2021 and in May 2023 to assess the hospital's improvements in its COVID-19 readiness capacity by collecting data on the hospital's characteristics and using the WHO COVID-19 Rapid hospital readiness checklist. We scored each readiness indicator according to the WHO criteria and the hospital's overall readiness score, performed the chi-square test for the change in readiness (change, 95%CI, p-value) between 2021 and 2023, and classified the center's readiness (poor: <50%, fair: 50-79%, or satisfactory: ≥80%). The overall hospital readiness for COVID-19 response was poor in 2021 (mean score=49%, 95% CI: 39%-57% and fair in 2023 (mean score=69%, 95%CI: 56%-81%). The mean change in hospital readiness was 20% (95% CI: 5.7%-35%, p-value=0.009). Between 2021 and 2023, the hospital made satisfactory improvements in leadership and incident management system (from 57% in 2021 to 86% in 2023 [change=29%, 95%CI:17%-41%, p<0.001]); risk communication and community engagement (38% to 88% [change=50%, 95%CI: 39%-61%, p<0.001]); patient management (63% to 88% [change=25%, 95%CI: 14%-36%, p<0.001]); and rapid identification and diagnosis (67% to 83% [change=16%, 95%CI:4.2%-28%, p=0.009]). The hospital made fair but significant improvements in coordination and communication (42% to 75% [change=33%, 95%CI: 20%-46%, p<0.001]), human resources capacity (33% to 75% [change=42%, 95%CI: 29%-55%, p<0.001]), continuity of essential support services (50% to 75% [PD=25%, 95%CI: 12%-38%, p<0.001]) and IPC (38% to 63% [change=25% (12%-38%, p<0.001]) and no or unsatisfactory improvement in surveillance and 2 information management, administration, finance, and business continuity, surge capacity, and occupational, mental health psychosocial support.Substantial gaps still remain in the hospital's readiness to respond to the COVID-19 outbreak. The study highlights the urgent need for investment in resilient strategies to boost readiness to respond to future outbreaks at the hospital.